2013
DOI: 10.5702/massspectrometry.s0005
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of Non-Covalent Ion–Molecule Interactions

Abstract: The thermochemistry of non-covalent ion-molecule complexes has been examined by measuring quantitative bond dissociation energies using threshold collision-induced dissociation in guided ion beam tandem mass spectrometers (GIBMS). The methods used are briefly reviewed and several examples of the types of information and insight that can be obtained from such thermodynamic information are discussed. The hydration of metal cations, both singly and doubly charged, is reviewed and the trends elucidated, mainly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…H‐G complexes have been subjected to various mass spectrometry‐based studies with a variety of purposes such as measurement of the energetics of H‐G binding using blackbody infrared radiative dissociation (BIRD) or threshold collision induced dissociation (TCID), obtaining a relative ranking of the stabilities of H‐G complexes by comparing fragmentation efficiency (or survival yield [SY]) curves, studying the role of proton affinities of guest molecules on the characteristics of fragmentation spectra of H‐G complexes, exploring the structure of H‐G complexes and the interactions between the two partners using the Förster resonance energy transfer (FRET) technique, quantifying binding affinities by mass spectrometric titration, and exploring the influence of solvent on H‐G affinities . These kinds of gas‐phase studies, however, have been never employed for the study of hemicryptophane H‐G complexes.…”
Section: Introductionmentioning
confidence: 99%
“…H‐G complexes have been subjected to various mass spectrometry‐based studies with a variety of purposes such as measurement of the energetics of H‐G binding using blackbody infrared radiative dissociation (BIRD) or threshold collision induced dissociation (TCID), obtaining a relative ranking of the stabilities of H‐G complexes by comparing fragmentation efficiency (or survival yield [SY]) curves, studying the role of proton affinities of guest molecules on the characteristics of fragmentation spectra of H‐G complexes, exploring the structure of H‐G complexes and the interactions between the two partners using the Förster resonance energy transfer (FRET) technique, quantifying binding affinities by mass spectrometric titration, and exploring the influence of solvent on H‐G affinities . These kinds of gas‐phase studies, however, have been never employed for the study of hemicryptophane H‐G complexes.…”
Section: Introductionmentioning
confidence: 99%
“…When comparing the BDEs of the five alkali cations to any particular ligand, one finds that the values increase as the size of the metal cation decreases. [123][124][125] This is a simple electrostatic effect in that the smaller cation has a shorter bond distance leading to a stronger bond. Glycine, or for that matter any other amino acid or small peptide, is no exception.…”
Section: Periodic Trends In Binding Energiesmentioning
confidence: 99%
“…By contrast, up to now there exists no mass spectrometric method which has gained equal acceptance for investigating gas phase binding strengths of distinct protein-ligand complexes. Previous reports have shown that high pressure mass spectrometry and/or black body irradiation can be applied for analyzing small molecule-ion equilibria and to determine kinetic and thermodynamic properties, such as ion-ligand complex constants in the right order of magnitude [ 2 , 3 , 4 ] also for small peptides, the protonated glycine dimer being the smallest possible peptide dimer representative [ 5 ]. Gas phase dissociation reactions of Leu-enkephaline dimers [ 6 ] and of small proteins, such as ubiquitin [ 7 ] had been studied as well.…”
Section: Introductionmentioning
confidence: 99%